The problem of knowledge: Philosophy, science, and history since Hegel - Cassirer, Ernst 1874-1945 (London Yale University Press, 1950)
Cassirer employs his remarkable gift of lucidity to explain the major ideas and intellectual issues that emerged in the course of nineteenth century scientific and historical thinking. The translators have done an excellent job in reproducing his clarity in English. There is no better place for an intelligent reader to find out, with a minimum of technical language, what was really happening during the great intellectual movement between the age of Newton and our own."New York Times.